Dystopıan representatıon ın contemporary Turkısh cınema - Ünal, Umutcan (İstanbul Bilgi Üniversitesi, 2019)
ABSTRACT: Any fictional filmic world can be formed as dystopian, regardless of visual features of the place designed before the audience. It means that the fictional worlds with which the audience is familiar can also be evaluated under the concept of dystopia. Therefore, in the first chapter of this thesis, three criteria and some discursive elements, that are used to decide whether a film is dystopian or not, are proposed. In Chapter 2, it is shown that creating realistic worlds, that are almost inseperable from the actual world of the audience, within the dystopian tradition is possible. In the last chapter, three films from contemporary Turkish cinema, that are “Abluka” (Alper, 2015), “Sarmaşık” (Karaçelik, 2015) and “Babamın Kanatları” (Sezer, 2016), are analyzed, based on the criteria and the discursive elements presented in the first chapter. Although all three films take place in non-estranging place and time; it is shown that they can still be analyzed within the dystopian tradition, as in the other dystopian films with realistic settings which are presented in the second chapter. It is concluded that Abluka and Sarmaşık are dystopian films according to the criteria that is proposed, while Babamın Kanatları is not.

ÖZET: Her kurgusal film dünyası, seyirci karşısında kurulan mekanın görsel özellikleri dikkate alınmaksızın, distopik olarak kurulabilir. Bu, seyircinin aşina olduğu kurgusal dünyaların da distopya başlığı altında incelenebileceği anlamına gelir. Bu nedenle, bu tezin ilk bölümünde, bir filmin distopya olup olmadığına karar vermede kullanılan üç kriter ve bazı söylemsel elemanlar önerilmektedir. İkinci bölümde; distopya geleneği içinde, izleyicinin gerçekliğinden neredeyse ayrılamayacak kadar gerçekçi dünyalar yaratmanın mümkün olduğu gösterilmiştir. Son bölümde, bu kriterler ve söylemsel elemanlara dayanarak, çağdaş Türkiye sinemasından üç film, “Abluka” (Alper, 2015), “Sarmaşık” (Karaçelik, 2015) ve “Babamın Kanatları” (Sezer, 2016), analiz edilmiştir. Bu üç film yabancılaştırıcı olmayan mekan ve zamanda geçmesine rağmen, bu filmlerin distopya geleneği içerisinde değerlendirilebileceği gösterilmiştir; ikinci bölümde sunulan diğer gerçekçi sahneli distopik filmlerde olduğu gibi. Önerilen kriterlere göre Abluka ve Sarmaşık’ın distopya iken Babamın Kanatları’nın distopya olmadığı sonucuna varılmıştır.
Çağdaş Türk sinemasında distopya temsili
Keywords: dystopia; discourse analysis; misfit hero; estrangement; contemporary Turkish cinema; distopya; diskur analizi; uyumsuz kahraman; çağdaş Türk sineması; yabancılaşma